Civic capital and the size distribution of plants: Short-run dynamics and long-run equilibrium - Matthias Bürker; G. Alfredo Minerva (Fondazione Eni Enrico Mattei (FEEM), 2012)
We characterize how the size distribution of plants, within narrowly defined industries, changed in Italy over a ten-year time span, and relate this to the stock of civic capital at the provincial level. Data on plant size come from the 1991 and 2001 Italian censuses. Civic capital turns out to have a positive effect on both the average and standard deviation of size. Looking at several precise points of the plant size distribution, we find that it shifts toward the right and becomes more dispersed where civic capital is high. The potential endogeneity of current civic capital is addressed by instrumenting it with historical variables. Our main conclusion is that the geographic variation in the stock of civic capital poses substantial constraints on plants' ability to expand. Understanding this is the key for the implementation of effective industrial policies.
Keywords: A13; D23; L20; R12; 330; Civic Capital; Cooperation; Opportunism; Plant Size Distribution; Trust